Methodologies of impulse tests on earthing systems by field measurements with different remote earth - Yunus S.; Nor N.M.; Agbor N.; Othman M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Nowadays, with a good design and available facilities of high impulse generators that can be taken to field sites for measurements, much research work can be found on the field measurement on the study of the grounding under fast transients. Moreover, field tests on earthing systems have become interesting since it can provide the closest scenario of the characteristics of grounding system when fast transient current discharged to the earthing systems. However, the field measurements have some limitations on the standard methodologies that should be adopted during the field measurements. There is also very little being mentioned on the arrangements/values of the remote earth. As generally known, the remote/auxillary earth is important not only for the purpose of discharging any high fault current during the tests on the electrode under tests, but also to ensure that the remote earth is not being included in the measurements, hence affect the accuracy of the measurements. Due to these factors, this paper is to aimed to study how different configurations and resistance values of remote earth on the characteristics of main earthing systems. It was found that different results were obtained when higher earth resistance values of remote earth were used for impulse tests on main earthing systems. 2016 IEEE.